The Brave New World of clinical cancer research: Adaptive biomarker‐driven trials integrating clinical practice with clinical research1. Issue 5 (11th March 2015) - Berry, Donald A.
Abstract : Clinical trials are the final links in the chains of knowledge and for determining the roles of therapeutic advances. Unfortunately, in an important sense they are the weakest links. This article describes two designs that are being explored today: platform trials and basket trials. Both are attempting to merge clinical research and clinical practice.